1997
DOI: 10.1128/aac.41.6.1406
|View full text |Cite
|
Sign up to set email alerts
|

In vitro susceptibilities of clinical isolates of vancomycin-resistant enterococci

Abstract: Recent studies have reported RP59500 (Synercid) (quinupristin-dalfopristin), a semisynthetic streptogramin, to have good in vitro activity against certain enterococcal strains, including vancomycin-resistant strains of Enterococcus faecium (3-5). The purpose of the present study was to determine the in vitro activity of this new compound against a larger sample of resistant strains of enterococci and to compare its activity with those of several currently available antimicrobials. We analyzed 1,044 strains of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Bacitracin has limited oral absorption, has excellent in vitro activity against VRE [27], and has been shown to suppress bowel flora when Ͼ100,000 U daily is administered [28]. Doxycycline has in vitro activity [29,30], achieves adequate fecal levels [31] to have activity against VRE, and has shown clinical efficacy against VRE [17,30]. Nord and Heimdahl showed that administration of oral doxycycline for 7 days decreased the number of enterococci in the feces by 2-3 logs [31] but also led to a significant increase in doxycyclineresistant strains.…”
Section: Discussionmentioning
confidence: 98%
“…Bacitracin has limited oral absorption, has excellent in vitro activity against VRE [27], and has been shown to suppress bowel flora when Ͼ100,000 U daily is administered [28]. Doxycycline has in vitro activity [29,30], achieves adequate fecal levels [31] to have activity against VRE, and has shown clinical efficacy against VRE [17,30]. Nord and Heimdahl showed that administration of oral doxycycline for 7 days decreased the number of enterococci in the feces by 2-3 logs [31] but also led to a significant increase in doxycyclineresistant strains.…”
Section: Discussionmentioning
confidence: 98%
“…31 A report of in vitro susceptibilities of 1,044 strains of VRE (990 Enterococcus faecium and 54 Enterococcus faecalis) from New Jersey hospitals between 1993 and 1996 found that 92.1% of Enterococcus faecium strains, but only 68.5% of Enterococcus faecalis strains, were susceptible to chloramphenicol. 32 Transferable plasmids mediating resistance to multiple antibiotics, including chloramphenicol, are well known in Enterococcus faecalis. 11 We noted clustering of many cases of chloramphenicol-resistant VRE in two areas of the hospital (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental reservoirs of vana-type vancomycin-resistant enterococci (VRE) were first reported from Europe in 1993.16 These reservoirs are related to widespread use of the glycopeptide avoparcin as a growth-promoting feed additive in European animal husbandry.1 [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] carrying VRE in their gastrointestinal tract have been suggested as a likely source of VanA VRE infection in humans, 4 and several studies have focused on possible transmission lines between humans and animals. The occurrence of VRE in chicken carcasses and commercial meat products4 '17,19 im-plies the risk of VRE transmission through the food chain and could explain the detection of VRE in fecal samples from healthy volunteers,25 out-patients,17'25 and newly admitted hospital patients.5 A case of possible VRE transmission from colonized animal to human by direct wound inoculation was recently reported in a community-acquired infection in a food industry worker.7 This observation suggests a mode of VRE transmission through direct contact between humans and colonized animals.…”
Section: Introductionmentioning
confidence: 99%